A, The THE ROLE OF VILLAGE GOVERNMENT IN INCREASING THE INCOME OF THE DAIRY CATTLE FARM COMMUNITY: Peran Pemerintah Desa Dalam Meningkatkan Pendapatan Masyarakat Peternak Sapi Perah - Ahmad, Ahmad Virdiansyah (Publiciana, 2025)
This research aims to describe and explore the problems of the dairy farming community related to their low income and the efforts of the government of Kemiri Village, Jabung District, Malang Regency in overcoming these problems. This research uses a qualitative approach and case study strategy, data collection using in-depth interviews, field observations and utilizing secondary data documentation, then processed and analyzed using the Miles and Huberman interactive model where data validity uses data credibility standards. From the research results it can be concluded that the dairy farming business can still attract public interest, efforts to increase the quantity and quality of milk production still need assistance in terms of facilities and infrastructure. The conclusion shows that the work of dairy farmers is an important livelihood in the research location, the causal factors low income due to varied cattle ownership, inadequate road access, high livestock operational costs, cattle diseases and other supporting equipment. The village government's efforts include utilizing existing natural resources and strengthening social institutions. However, there are obstacles faced, including farming experience, milk filtering equipment, and varying cow ownership. Keywords: Village Government, Community Income, Dairy Cow Milk, Dairy Cattle Farmers